Peluang dan tantangan bimbingan karir di sekolah menengah kejuruan pada era revolusi industri 4.0 - Rima Pratiwi Fadli; Mudjiran Mudjiran; Ifdil Ifdil; Berru Amalianita (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The 4.0 industrial revolution brought various changes in various fields of life especially related to the development of individual careers. This development has positive and negative impacts that create opportunities and challenges. This has become material for BK / Counselor teachers, especially in the implementation of career guidance in schools. The following will be explained related to the opportunities and challenges of career guidance in vocational high schools in the industrial revolution era 4.0. This paper was written using a literature study of various references related to the topics discussed. Reference literature in this manuscript is from textbooks, scientific journals of research results, online proceedings, and other supporting literature.